Perbandingan Kurikulum 13 dan Kurikulum Merdeka Ditinjau dari Aspek Asesmen Pembelajaran di SDN 180 Prakarsa Nugraha Arcamanik Kota Bandung - Ainurrahmah, Aina; Nugraha, Hadi; Widianto, Rizki; Rigandani, Suci Rahayu; Pujawardani, Hani Hadiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to compare the 2013 Curriculum and the Independent Curriculum from the perspective of learning evaluation at SDN 180 Prakarsa Nugraha. The method applied in this study is a combined approach, which includes data collection through interviews and direct observation in the field. The results of the study indicate significant differences in assessment methods between the two curricula, where the 2013 Curriculum focuses more on tests and exams, while the Independent Curriculum emphasizes project- based assessments. The average final score of students studying with the Independent Curriculum reached 85, while students following the 2013 Curriculum only got 78. In addition, challenges faced by teachers in implementing assessment have also been identified, such as the high administrative burden in the 2013 Curriculum and the lack of understanding of project assessment in the Independent Curriculum. The results of this study indicate that the Independent Curriculum has a better effect on student learning achievement and encourages their active participation in the learning process. This research is expected to contribute to the advancement of educational policies and more effective teaching methods.